POLA KOMUNIKASI KEPEMIMPINAN KEPALA MADRASAH DALAM MENGELOLA PEMBINAAN AKHLAK PESERTA DIDIK PADA MADRASAH ALIYAH NEGERI 2 MODEL PALU - Sanimbar Mustafa; Andi Anirah (ISTIQRA, 2016)
This study discusses communication patterns headmaster manage moral guidance of learners in Madrasah Aliyah Negeri 2 Model Palu. This study uses qualitative methods with data collection through observation, structured interviews and document madrasah. Mechanical analysis of data through data reduction, display data and verification of data, drawing conclusions appropriate focus of research. The results showed that: 1) Communication patterns head Madrasah Aliyah Negeri 2 Model Palu use interactional patterns of communication and psychological communication patterns. Interactional communication pattern used in communicating to the deputy headmaster, the teachers democratically. Psychological communication pattern used to communicate to students who are directing, motivating and exemplary; 2) Management coaching morals implemented in two forms namely through better planning and implementation of development programs fostering moral character spontaneously by the headmaster and teachers at MAN 2 Model Palu; 3) Application of communication patterns interactional headmaster to the deputy headmaster, the teachers, staff other and communication patterns psychological headmaster to learners is very effective in managing the coaching morals learners, evidenced by the atmosphere of habituation salute, habituation tadarus al-Qur / initiate an every subject matter in the morning, pray together starting and closing subjects, refracting prayers and giving Kultum after noon prayers at the mosque, habituation equal cooperation, habituation in organizing fellow learners, provision of material in all subjects morals that teached in the classroom and taught at boarding school programs can influence the character peseta students in MAN 2 Model Palu